ANALISIS MODEL FLIPPED CLASSROOM SEBAGAI ALTERNATIF PENGUATAN KARAKTER ENTREPRENEURSHIP SISWA - Arsya Ma’wa Ni’matul Izzati; Ferida Rahmawati; Siti Nur Azizah; Farah Abidah Maryam; Wildan Khairil Anam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education plays a vital role in shaping a young generation that is adaptable, creative, and innovative in facing the changing times. This study aims to explore and analyze the flipped classroom model as an alternative learning approach, with a focus on strengthening students’ entrepreneurial character. A descriptive approach was used to detail the concept, implementation, strengths and weaknesses, as well as the correlation between the flipped classroom model and the strengthening of entrepreneurial character. The data used in this study are secondary, obtained through literature reviews, documents, and other relevant sources by analyzing several scientific articles related to entrepreneurship character education methods. The results of the study indicate that the flipped classroom model provides a more interactive and meaningful learning experience for students in understanding and internalizing entrepreneurial values. Supporting factors include the teacher’s role as a facilitator, student autonomy, and the quality of learning activities. On the other hand, barriers include resistance to change and a lack of preparation.